Strategi Dakwah Tarekat Qadiriyah wa Naqsabandiyah di Desa Bluto Kec. Bluto Kab. Sumenep - Krisdiantoro; Tabaika, Mohammad A’lan (Journal of Islamic Communication Studies, 2023)
The advancement of world civilization has brought society into the era of modernity, which forms a society that tends to be materialistic and puts aside the spiritual side. Tarekat Qodiriyah wa Naqsabandiyah is a tarekat group that is consistent with the spiritual side of humans. This research aims to find out the Qodiriyah wa Naqsabandiyah tarekat's da'wah strategy. This research uses a phenomenological approach with a qualitative research type. Data collection techniques include interviews and observations. The da'wah uses a sentimental strategy, which focuses on the inner feelings of its da'wah partners through sharing, discussion. The strategies applied in preaching are individual approaches and collective approaches. Individual da'wah is carried out by providing individual spiritual guidance. This spiritual guidance is intended so that an individual always taqarrub to Allah Subhanahu Wa Ta'ala. While collective da'wah is aimed at a group of people, in this case, a group of people can be followers of Tarekat Qadiriyah wa Naqsabandiyah or people who have not become members of the order.